(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The study was undertaken to know the distribution pattern, morphometric characteristics, production and reproduction peculiarities of White, Silver Bezoar and Black coated types of Black Bengal goat in Sylhet, Mymensingh and Bogra region of Bangladesh. Live weight, body measurements, hair diameter and density per unit area were directly obtained from animals. Milk production, life span, number of kidding and other behavioural data (0-5 score) were collected by interviewing farmersThe proportion of White type linearly decreased from east (30% in Sylhet) to west (18% in Bogra) but an erratic fashion was observed in Silver Bezoar type. White type was significantly (p<0.001) heavier at 3, 6, 9 and 12 month among the groups. Body length behaved similarly although heart girth and height at wither showed irregular pattern between groups. White goat possessed coarser but Black goat had more dense (p<0.01) hair at flank and thigh. Herding tendency, resting in crowdy place, grazing habit (p<0.001) of White type was higher than its contemporaries. Average milk yield (g/day) was higher (p<0.05) in White type (366.84) than Black (248.83) and Silver Bezoar types (274.16). Above findings suggest that White and Silver Bezoar types of Black Bengal goat are superior to Black coated goats and thus demand due attention in order for their conservation. Further study is needed for genetic characterization for final recommendation. Keywords: Black Bengal goat; White type; Silver Bezoar type; Coat color; Hair density DOI: 10.3329/jbau.v7i2.4740 J. Bangladesh Agril. Univ. 7(2): 309-315, 2009